Impact of chronic transcranial random noise stimulation (tRNS) on GABAergic and glutamatergic activity markers in the prefrontal cortex of juvenile mice - Sánchez-León, C.A.; Sánchez-López, Á.; Gómez-Climent, María Ángeles; Cordones, I.; Cohen Kadosh, R.; Márquez-Ruiz, J. (Elsevier B.V., 2022)
Transcranial random noise stimulation (tRNS), a non-invasive neuromodulatory technique capable of altering cortical activity, has been proposed to improve the signal-to-noise ratio at the neuronal level and the sensitivity of the neurons following an inverted U-function. The aim of this study was to examine the effects of tRNS on vGLUT1 and GAD 65–67 and its safety in terms of pathological changes. For that, juvenile mice were randomly distributed in three different groups: “tRNS 1 ×” receiving tRNS at the density current used in humans (0.3 A/m2, 20 min), “tRNS 100 ×” receiving tRNS at two orders of magnitude higher (30.0 A/m2, 20 min) and “sham” (0.3 A/m2, 15 s). Nine tRNS sessions during 5 weeks were administered to the prefrontal cortex of awake animals. No detectable tissue macroscopic lesions were observed after tRNS sessions. Post-stimulation immunohistochemical analysis of GAD 65–67 and vGLUT1 immunoreactivity showed reduced GAD 65–67 immunoreactivity levels in the region directly beneath the electrode for tRNS 1 × group with no significant effects in the tRNS 100 × nor sham group. The observed results suggest an excitatory effect associated with a decrease in GABA levels in absence of major histopathological alterations providing a novel mechanistic explanation for tRNS effects. © 2021 Elsevier B.V.
Keywords: cortical excitability; GABA; non-invasive brain stimulation; prefrontal cortex; tES; tRNS; Scopus(2); JCR